PENGARUH LAYANAN BIMBINGAN KONSELING TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS 3 SD NEGERI PASIR GOMBONG 06 KABUPATEN BEKASI - Ira Restu Kurnia; Nurmalia; Sri Rahayu; Nadhia Fatmawati; Aliya Rahmawati; Farahdila; Kristina Handayani; Siti Komariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education in Indonesia is strongly influenced by the times and the development of the times will have a majorinfluence on child development, problems that occur in the world of education are nothing more than the problem of child delinquency in schools, this shows the importance of the role of counseling guidance servicesfor students when they are in situations that they think do not make them comfortable and this will have animpact on learning carried out in the classroom Because of the lack of learning motivation that learners havebecause of the discomfort itself. The purpose of this study is to find out the problems that often occur inschools that make students uncomfortable during the learning process so that their learning motivationdecreases and try to find solutions to these problems so that students can feel comfortable, safe and happy inlearning so that their learning motivation will increase and this will affect the learning outcomes of students.The research method used is a qualitative description approach by conducting direct observations andinterviews at SDN Pasir Gombong 06 to identify whether there are problems that occur in the learning processthat result in lack of student motivation and using data analysis related to various sources so as to strengthenthe assumptions in the research we conducted. The results of this study are: 1) students feel comfortable andsafe when there are adults watching them 2) students are more open in telling their problems when we askquestions well and slowly 3) students better understand how to act in class both towards educators andclassmates 4) student learning motivation increases when they are happy and happy 5) students explorethemselves in their own way, namely Such as: making noise because you want to be noticed or always askingquestions because you want to be listened to .